Photonic Filters Using Optical Retarders Based on Birefringent Optical Media - Santos Aguilar, Joel; Guti´´errez Martínez, Celso (Revista de Ciencias, 2015)
Photonic filters can be used for filtering the spectrum of wide-band optical sources such as light emitting diodes (LED)  or multimode laser diodes(MMLD). In this work the use of birefringen optical media such as polarization maintaining fiber (PMF) or birefringent optical waveguides on Lithium Niobate (LiNbO3) crystal, perform as optical filters.